Cervicofacial Infections Caused by Staphylococcus aureus - Lazarte, Carlos (Ann Maxillofac Surg, 2019)
Staphylococcus aureus (S. aureus) is an opportunistic pathogen that causes a wide range of diseases. Dissemination of perioral infections is a common problem in the field of oral and maxillofacial surgery. The aim of the study was to evaluate S. aureus carriage in the oral cavity and its dissemination to different cervicofacial regions. Clinical case 1 is a patient with a systemic history of type I diabetes which led to foot amputation one year previou sly, who presented alteration of ocular motility and the culture showed Grampositive cocci compatible with S. aureus. The patient was discharged after eight days of antibiotic therapy and drainage. Clinical case 2 was a young female without any comorbidities who had never been hospitalized before or even exposed to the hospital environment. The presence of lesions compatible with necrotizing fasciitis (NF) in the lower lip mucosal region, rapid evolution of the infection to deep planes, and evolution of the clinical picture alerted health-care providers to the need for prompt care. Clinical case 3 was an immunosuppressed patient with cellulitis which is a bacterial infection of the skin and soft tissues that occurs when the physical barrier of the skin and soft tissues, the immune system, and/or the circulatory system are affected. S. aureus is an opportunistic pathogen which causes a wide range of diseases. It inhabits the oral cavity, from where it can spread to distant cervicofacial regions. This is why it is important for health-care professionals to be aware of this niche in case of dissemination in order to provide prompt diagnosis and appropriate treatment.